An exploration of process oriented guided inquiry learning in undergraduate Chemistry classes - Vishnumolakala, Venkat Rao (Curtin University, 2013)
The research study explored student’s understanding of stereochemistry and their perceptions of learning chemistry in first year undergraduate chemistry classes following a modified Process-Oriented Guided Inquiry Learning (POGIL) that included group work. A 5-item two-tier stereochemistry concept diagnostic test (SCDT) was developed and administered to explore their understanding of stereochemistry concepts. The students’ perception of POGIL learning was gauged in an effort to establish construct and convergent validity to the SALG instrument.